Standardization and harmonization in hematology: Instrument alignment, quality control materials, and commutability issue. (10th November 2020) - Vidali, Matteo; Carobene, Anna; Apassiti Esposito, Sara; Napolitano, Gavino; Caracciolo, Alessandra; Seghezzi, Michela; Previtali, Giulia; Lippi, Giuseppe; Buoro, Sabrina
Abstract: Introduction: In the hub and spoke laboratory network, the number of hematology analyzers (HAs) within each core center has increased, and the control of HAs alignment is becoming necessary requirement to ensure analytical quality. In this scenario, HA alignment can be assessed by analyzing the same control material used for internal quality control on multiple HAs, assuming its commutability. The aim of the study was to verify the applicability of a protocol for the alignment of HAs based on control material rather than on fresh whole‐blood samples. Methods: The alignment of five HAs was evaluated for red (RBC, Hb, MCV, RET), white (WBC, NE, LY, MO, EO, BA, IG), and platelet (PLT) series parameters, following a protocol by SIBioC, using human sample (HS) and quality control material (QC), after the verification of commutability, according to the IFCC protocol. Maximum bias was derived from biological variation data. Results: A complete alignment between instruments was confirmed for the majority of the parameters investigated both for HS and QC material. Partial misalignments or inconcludent results were instead evident for MCV, MO, EO, BA, and IG. Interestingly, QC material was found to be not commutable for LY, MO, and BA. Conclusion: The alignment of hematologic analyzers for main cell population parameters may be verified with both QC and HS, displaying consistent results and interpretation. The evaluation for some white series parameters (EO, BA, and IG) is critical, and particular attention must be paid to the values of the material used for the alignment.